Promoting Twenty-first-century Student Competencies: A Wellbeing Approach. Issue 3 (3rd July 2017) - Whiteside, Mary; Bould, Emma; Tsey, Komla; Venville, Annie; Cadet-James, Yvonne; Morris, Meg E.
ABSTRACT: In Australia and internationally, universities are preparing students for the twenty-first century through building the competencies fundamental for both social sustainability and wellbeing. However, there is little evidence on how these competencies can be fostered in curricula. This article presents the findings of a mixed-methods pilot of an Aboriginal wellbeing intervention that seeks to build such attributes when integrated into an undergraduate social work curriculum. A questionnaire incorporating the validated Growth and Empowerment Measure, the Australian Unity Personal Wellbeing Index, and open-ended qualitative questions was administrated to 64 first-year social work students before and after the intervention. Significant changes on both measures suggest that the intervention is highly relevant for student wellbeing, particularly for those who rated themselves as below the median at baseline. The qualitative findings highlight the relevance of the program for promoting social competencies that enable people to problem-solve and adapt in a complex world.